Workforce Characteristics, Work Satisfaction, Stress, Burnout and Happiness of Early Career Music Therapists in the United States - Anthony Meadows; Lillian Eyre; Audra Gollenberg (Voices)
As part of a larger, multi-step survey, 507 early career music therapists in the United States completed a series of 26 survey questions that focused on their work lives, stress, burnout and happiness. Descriptive analysis of responses to these questions suggest the majority of these early career professionals were satisfied with their jobs and work conditions, and worked in ways they found fulfilling and meaningful. However, these data also suggest a number of challenges for early career professionals that included low salary satisfaction, high stress and burnout, and overall lower happiness than music therapists with more work experience. In particular, low levels of access to supervision and support for continuing education suggest that some early career music therapists may not be receiving the professional support they need to grow and thrive. Recommendations, along with focus areas for additional research, provide a lens through which these concerns may be addressed.